Laser drilling of hollow sphere structures. Issue 5 (May 2014) - Riegel, H.; Merkel1, M.; Öchsner, A.
<x xml:space="preserve">Abstract</x> A special composite and cellular material – the metallic hollow sphere structure (MHSS) – represents an advanced material. The core element of the structure is a hollow sphere with a wall out of porous steel. This shell allows a high geometric reproducibility. It is an interesting base material for lightweight design. However, processing technologies for further manufacturing of metallic hollow sphere structure are necessary. Laser beam drilling is a highly efficient technique with heat input concentrated locally at the structure. Laser drilling is applied to metallic hollow sphere structures. The influence of different geometries and joining technologies of the spheres on the drilling behaviour is investigated. Percussion drilling is used to form holes with a CO2‐laser into the metallic hollow sphere structure. The investigated mean laser power is 400 W. Two different focal lenses with focal lengths of 5″ and 7.5″ allow investigations with different focal diameters and Rayleigh lengths. Diameter and roundness of the laser drilled holes are measured in five layers of different drill depths z. The maximum drilled depth is about 40 mm with a 5″ lense and about 50 mm with the f = 7.5″ lens. The relative roundness is determined and decreases with increasing drill depth. The diameter d(z) as a function of the drill depth follows the shape of an isophote, a line of constant intensity inside the laser beam. The brazed hollow sphere structures have considerably less drill depth than the sintered.